Evaluasi Pengaruh Teknologi Pruning pada Berbagai Usia Pertanaman terhadap Mutu Benih Padi (Oryza sativa L.) - Annisa Khoiriyah; Elea Nur Aziza; Geraldo Adinugra Rimartin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aimed to analyze the effects of pruning at different crop ages on the physical, physiological, and biochemical quality of rice seeds, as well as to identify seed responses to variations in pruning timing. The experiment was conducted using a non-factorial Completely Randomized Design on the rice variety Inpari 32. Four pruning treatments were applied, namely no pruning (P0), pruning at 25 days after transplanting (DAT) (P1), 35 DAT (P2), and 45 DAT (P3), with three replications for each treatment. Observations focused on physical seed quality parameters, including moisture content, seed purity, and 1000-seed weight, as well as physiological seed quality parameters, namely germination percentage, vigor index, growth rate, rapid emergence (RE), percentage of normal seedlings, percentage of non-emerged fresh weight, and seed biochemical composition (total sugars, starch, and carbohydrates). Data were analyzed using analysis of variance (ANOVA) at a 5% significance level, followed by Duncan’s Multiple Range Test. The results revealed that pruning treatments did not significantly affect moisture content, seed purity, growth rate, germination percentage, vigor index, rapid emergence, percentage of abnormal seedlings, non-emerged fresh weight, starch content, or carbohydrate content. However, the highest 1000-seed weight was observed in the non-pruned treatment. In contrast, pruning at 35 DAT resulted in the highest total sugar content compared to other treatments, indicating its potential contribution to improved seed physiological quality. These findings suggest that pruning at an appropriate growth stage may influence specific seed quality attributes, particularly biochemical characteristics.